Dental Knowledge, Behaviors, and Patterns of Missing Teeth - waleed, Rayan Waseem; Abdulwahab , Nagwan Ali; Mahdi , Aya Hamid (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Oral health knowledge and daily behaviors are essential determinants of tooth retention, yet limited awareness of preventive practices continues to contribute to avoidable tooth loss. Specific Background: In many communities, dental floss use, fluoride awareness, and dietary control remain inadequate despite regular toothbrushing habits. Knowledge Gap: Few studies have examined how these behavioral and knowledge-related factors correspond with the number and distribution of missing teeth among adults. Aim: This study assessed dental knowledge, oral hygiene behaviors, and dietary habits in relation to the number of missing teeth in adult patients. Results: Most participants had more than five missing teeth, predominantly in the lower posterior region. Very few used dental floss, many consumed sweets and sweetened drinks between meals, and awareness of fluoride was notably low. Participants often visited the dentist only when in pain and lacked proper instruction on flossing technique. Novelty: The study provides combined behavioral–knowledge profiling linked to quadrant-specific tooth loss within a middle-aged population. Implications: Findings underscore the need for strengthened preventive programs emphasizing dietary counseling, proper interdental cleaning, and improved fluoride awareness to reduce future tooth loss. Highlights: Most missing teeth were located in the lower posterior region. Fluoride and flossing knowledge remained low despite frequent brushing. High intake of sweets and delayed dental visits contributed to tooth loss. Keywords: Dental Knowledge; Oral Hygiene Behavior; Missing Teeth; Fluoride Awareness; Dietary Habits